-2a+24+8a=4a-6a

Simple and best practice solution for -2a+24+8a=4a-6a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a+24+8a=4a-6a equation:


Simplifying
-2a + 24 + 8a = 4a + -6a

Reorder the terms:
24 + -2a + 8a = 4a + -6a

Combine like terms: -2a + 8a = 6a
24 + 6a = 4a + -6a

Combine like terms: 4a + -6a = -2a
24 + 6a = -2a

Solving
24 + 6a = -2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2a' to each side of the equation.
24 + 6a + 2a = -2a + 2a

Combine like terms: 6a + 2a = 8a
24 + 8a = -2a + 2a

Combine like terms: -2a + 2a = 0
24 + 8a = 0

Add '-24' to each side of the equation.
24 + -24 + 8a = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 8a = 0 + -24
8a = 0 + -24

Combine like terms: 0 + -24 = -24
8a = -24

Divide each side by '8'.
a = -3

Simplifying
a = -3

See similar equations:

| 6z-13-z+3=0 | | 3/4t=-48 | | 12/-4/9 | | 4y+2y=5y-2 | | 2(4x-8)+6(5x+2)=6(4x+9)3 | | 3a^2-8a-24a+64= | | 9+m/=2 | | 6x-9+4x=51 | | -1-5x=-26 | | 5(5y-4)-8y= | | 2x^2-6x-2ax+8+a^2=x-1 | | x^3-37x+84=0 | | 80+60+x+51=180 | | (3x-1)-3(2x+3)+42=2x(-x-5)-(x-1) | | 6x+x-6=6x+4 | | 6w-4+4=-3+3+4 | | 2x-6=5x+18-3(x-4) | | -(w+4)=-8w+9 | | 10x+8-5x-3=-16 | | 200+15x=424 | | -4s^2-11s=-3 | | 3-3x=-27 | | (3p-6)=90 | | 7g-5-3-7g= | | 5x+6=-3+2x+18 | | -3(x-6)=66 | | 5=a/4+8 | | 21=-4 | | 4x^4-10x^2= | | 7x+8+6x=21 | | 2(4x-2)+2(7x+5)=512 | | 2x^2-6x-2ax+8+a^2=0 |

Equations solver categories